2011
DOI: 10.1007/s13534-011-0019-6
|View full text |Cite
|
Sign up to set email alerts
|

Positron emission tomography (PET) detectors with depth-of- interaction (DOI) capability

Abstract: Because positron emission tomography (PET) provides biochemical information in vivo with the sensitivity at the sub-pico-molar level, pre-clinical research using PET plays an important role in biological and pharmaceutical sciences. However, small animal imaging by PET has been challenging with respect to spatial resolution and sensitivity due to the small volume of the imaging objects. A DOI-encoding technique allows for pre-clinical PET to simultaneously achieve high spatial resolution and high sensitivity. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
109
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
10

Relationship

5
5

Authors

Journals

citations
Cited by 150 publications
(115 citation statements)
references
References 83 publications
(91 reference statements)
1
109
0
1
Order By: Relevance
“…The traditional multiplexing method used in this study for reducing the number of readout channels (21) somewhat degrades timing and counting rate performances, which can be improved using digital SiPM technology or novel sampling theory (37,38). The improved spatial resolution without the loss of sensitivity will also be possible via the incorporation of depth-ofinteraction measurement technology in PET detector modules (39). In addition, incorporating a total variation minimization algorithm into imaging reconstruction will be useful to improve image quality by reducing gap artifact (40).…”
Section: Discussionmentioning
confidence: 99%
“…The traditional multiplexing method used in this study for reducing the number of readout channels (21) somewhat degrades timing and counting rate performances, which can be improved using digital SiPM technology or novel sampling theory (37,38). The improved spatial resolution without the loss of sensitivity will also be possible via the incorporation of depth-ofinteraction measurement technology in PET detector modules (39). In addition, incorporating a total variation minimization algorithm into imaging reconstruction will be useful to improve image quality by reducing gap artifact (40).…”
Section: Discussionmentioning
confidence: 99%
“…To enhance sensitivity by elongating crystals, depth-of-interaction determination within crystals will be necessary to avoid the deterioration in spatial resolution uniformity (31). Several groups have shown that depth-ofinteraction encoding with SiPM is feasible (13).…”
Section: Discussionmentioning
confidence: 99%
“…More available space inside the MRI bore than is allowed in dedicated animal MRI scanners is another merit of the clinical MRI system. The larger space allows the use of longer scintillation crystals and various depth-ofinteraction measurement techniques to improve PET system performance (29).…”
Section: Discussionmentioning
confidence: 99%